ANALYSIS OF RELATIONSHIP BETWEEN OCCUPATIONAL SAFETY BEHAVIOR AND THE USE OF PERSONAL PROTECTIVE EQUIPMENT THE SHIP’S CREW - Diyah Purwitasari (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research focused on analyzing the relationship between work safety behavior and the usage of PPE (Personal Protective Equipment) on board. The safety of the ship's crew at work must be considered because accidents can happen at any time. To support safety, the ship's crew needs to be equipped with disciplined behavior while working. Like when doing work that is required to use of safety equipment. If this behavior is used as a discipline while working, then the ship's crew can avoid accidents. This research was conducted for 12 months. Data was collected through direct documentation, observation of the ship's crew while working, and giving questionnaires to determine the work safety behavior of the ship's crew. Based on the correlation test with Simple Linear Regression Analysis, it turns out that there is a good and significant relationship between the use of PPE on the safety behavior of ship crews. This is evidenced by the correlation equation with a coefficient (r) of 0.903 (in the form of a positive relationship). This means that if the PPE usage variable increases, it will be followed by the work safety behavior variable which also increases and vice versa.